Експресія гена аполіпопротеїну А-1 людини під контролем різних регуляторних послідовностей стабільними трансформантами СНО-К1 - Гільчук, Ю.М.; Сухорада, О.М.; Рубан, Т.А.; Іродов, Д.М.; Топорова, О.К.; Кордюм, В.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The recombinant plasmids (pTRapo-neoR, pTRapohCMVintronA-neoR, and pTRapohCMV β-actin-neoR) containing the human genomic apolipoprotein A-1 (apoA-1) gene under control of several transcriptional regulatory elements and neomycinphosphotransferase gene (neoR) have been constructed. The expression of human apoA-1 gene for all pools of stable transformants has been detected. А higher level of the expression of the transgene for pools obtained by the transfection with pTRapohCMVintronA-neoR and pTRapohCMV β-actin-neoR than that with pTRapo-neoR has been shown.